Pemberdayaan Desa Leuwimalang melalui Pengembangan Website Pariwisata dan Pemesanan Homestay - Latianingsih, Nining; Mariam, Iis; Chandra, Yanita Ella N.; Pratama, Arizal P.; Triyanto, Irfan Rusydi (Ma'soem University, 2025)
Leuwimalang Village, located in Cisarua District, Bogor Regency, possesses significant natural and cultural tourism potential; however, its utilization remains limited due to the lack of information and digital-based promotion. This community service activity aims to develop the village website as an information and promotional medium, particularly for homestay booking services and tour packages. The implementation method included field observation, problem identification in collaboration with village partners, and website content management. The results of the activity produced a digital platform containing structured information on tourism potential, homestay packages, travel guides, and the village profile. This website facilitates tourists in accessing information and making bookings, while also supporting homestay owners to promote their services. The application of this innovation is expected to enhance Leuwimalang Village’s competitiveness as a tourist village and contribute positively to the local community’s economy.